EFFECT OF LONG-TERM EXPOSURE TO LOWER LOW-DENSILIPOPROTEIN CHOLESTEROL BEGINNING EARLY IN LIFE ON THE RISK OF CORONARY HEART DISEASE. A MENDELIAN RANDOMIZATION ANALYSIS - B. A. Ference; W. Yoo; I. Alesh; N. Mahajan; K. K. Mirowska; A. Mewada; J. Kahn; L. Afonso; K. A. Williams; J. M. Flack (Столичная издательская компания, 2015)
Translation articles: B.A. Ference, W. Yoo, I. Alesh, N. Mahajan, K.K. Mirowska, A. Mewada, J. Kahn, L. Afonso, K.A. Williams, J.M. Flack «Effect of Long-Term Exposure to Lower Low-Density Lipoprotein Cholesterol Beginning Early in Life on the Risk of Coronary Heart Disease. A Mendelian Randomization Analysis» впервые опубликована в журнале J Am Coll Cardiol 2012; 60(25): 2631-9; doi:10.1016/j.jacc.2012.09.017 © 2012 by the AmericanCollegeofCardiology Foundation